Benefits and Advantages of Mediation - Tillaboyeva Muazzamoy (Research Parks Publishers, 2021)
Mediation is a structured, interactive process where an impartial third party assists disputing parties in resolving conflict through the use of specialized communication and negotiation techniques. All participants in mediation are encouraged to actively participate in the process. Mediation is a